When Zachary Beaver came to town - Holt, Kimberly Willis (Square Fish, 2011)
During the summer of 1971 in a small Texas town, thirteen-year-old Toby and his best friend Cal meet the star of a sideshow act, 600-pound Zachary, the fattest boy in the world.